The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.1128/mcb.00001-18
|View full text |Cite
|
Sign up to set email alerts
|

Mutant Isocitrate Dehydrogenase 1 Disrupts PKM2–β-Catenin–BRG1 Transcriptional Network-Driven CD47 Expression

Abstract: A gain-of-function mutation in isocitrate dehydrogenase 1 (IDH1) affects immune surveillance in gliomas. As elevated CD47 levels are associated with immune evasion in cancers, its status in gliomas harboring mutant IDH1 (IDH1-MT cells) was investigated. Decreased CD47 expression in IDH1-R132H-overexpressing cells was accompanied by diminished nuclear β-catenin, pyruvate kinase isoform M2 (PKM2), and TCF4 levels compared to those in cells harboring wild-type IDH1 (IDH1-WT cells). The inhibition of β-catenin in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 55 publications
1
12
0
Order By: Relevance
“…The reverse effect was observed in the same cells upon the pharmacological elevation of nuclear β-catenin levels. As expected, the CD47 transcriptional downregulation negatively affected the phagocytosis of cancer cells by microglia (158).…”
Section: Impaired Dcs Recruitment: Ccl4 Inhibitionsupporting
confidence: 79%
See 1 more Smart Citation
“…The reverse effect was observed in the same cells upon the pharmacological elevation of nuclear β-catenin levels. As expected, the CD47 transcriptional downregulation negatively affected the phagocytosis of cancer cells by microglia (158).…”
Section: Impaired Dcs Recruitment: Ccl4 Inhibitionsupporting
confidence: 79%
“…Various transcription factors have been proposed to bind to the promoter of CD47 and explain its upregulated expression in different tumors. Some of them like NF-κB, MYC, SNAI1, ZEB1, HIF-1 and the PKM2-β-catenin-BRG1-TCF4 complex (134,148,157,158) have been implicated in CD47 expression, which strongly suggests that the WNT/β-catenin pathway is involved (Figure 4). Supporting this idea, it has been shown that a constant activation of β-catenin is needed for glioma progression (159), and increased levels of its target genes, such as CD47, have been associated with high-grade GBM (16).…”
Section: Impaired Dcs Recruitment: Ccl4 Inhibitionmentioning
confidence: 99%
“…Interestingly, in human breast and lung cancer cell lines, inhibition of the Wnt pathway caused the down modulation of NK cell ligands favoring the evasion from the immune surveillance in this tumor sub-type population [ 219 ]. The contribution of the Wnt pathway to immune evasion is exerted by modulating “marker of self” and “don’t eat me” molecules, such as CD47 [ 220 ], which impair the phagocytic activity of macrophages and dendritic cells [ 221 ]. Furthermore, PD-L1 expression is tightly regulated by the Wnt pathway in triple negative breast cancer [ 222 ].…”
Section: Genetic Mechanisms Of Immune Evasion In Msi Crcmentioning
confidence: 99%
“…The immune checkpoint protein CD47 is included in the list of Wnt/β-catenin target molecules with a role in immunity escape. 17 Since β-catenin depletion by siRNA inhibited the expression of CD47 ( Figure 6A), we then sought to know whether erianin regulates the expression of CD47. First, we explored the effects of erianin on CD47 mRNA, protein, and cell surface level.…”
Section: Erianin Decreased Cd47 Expression and Increased Phagocytosismentioning
confidence: 99%